Bahasa Inggris - Syahpitri, Eliana; Siregar, Nina Siti Salmiah; Batubara, Beby Masitho (Universitas Medan Area, 2025)
This study aims to analyze policy implementation, identify problems in SDI implementation, and recommend what strategies can be used in the successful implementation of SDI. This study uses a qualitative descriptive method to describe the implementation of SDI in Langkat Regency based on existing facts. Data was collected through observation, interviews, and documentation. The research informants consisted of the SDI Organizing Team, including Bappeda, BPS, Diskominfostand, and representatives of regional apparatus. The results of the study show that the implementation of SDI in Langkat Regency is still in the early stages and is not optimal. Efforts to catch up have been carried out with regulations, institutional formation, and the SDI Langkat Portal. However, various obstacles are still faced, such as suboptimal coordination between PDs, limitations of competent human resources in the field of statistics and data management, inadequate technological infrastructure, and low understanding and commitment to SDI principles. Awareness of the benefits of SDI is also minimal, so strategic steps are needed to increase the effectiveness of data governance in Langkat Regency